Efficacy of Ammonization to Eliminate Common Mycotoxins - Veysel Doğan; Armağan Hayırlı (Turkish Journal of Agriculture: Food Science and Technology)
Mycotoxin is a worldwide problem threatening animal health and performance as well as public health. The objective of this experiment was to test the effect of ammonization on elimination of common mycotoxins in laying hen compound feed (CF) and dairy cattle total mixed ration (TMR). The CF for laying hens and TMR for dairy cows were contaminated with commonly occurring mycotoxins [aflatoxin B1 (AFB1), ochratoxin A (OTA), and zearalenone (ZEA)] at 25 times of their accepted legal limits (20 ppb, 200 ppb and 500 ppb, respectively). They were then subjected to ammonization with ammonium bicarbonate (NH4HCO3) at 50C for 24 hours under the atmospheric pressure. Mycotoxin levels were analyzed using the LC-MS/MS technique. The elimination levels in CF and TMR were 53% and 54% for AFB1; 31% and 31% for OTA and 22% and 22% for ZEA, respectively. In conclusion, ammonization was effective in destroying common mycotoxin, at an order of AFB1 > OTA > ZEA.